(untitled) (Literatures of the World: Poetics, Mentality and Spirituality, 2020)
The article attempts to explore contemporary children’s literature of Kryvorizhzhia as a local-regional phenomenon of culture. The works of Inna Dolennik, Nina Yolkina, Mykola Oleksiienko, Ihor Rukavitsyn, Dmitriy Shcherbina and others were analyzed. It is established that the literature for children of preschool and primary school age is represented by the following genres: poems, riddles, fairy tales and stories. Intelligence has observed that works for children of the region are organically included in the common space of Ukrainian culture. They are geared to the needs of diverse reading groups and are designed to help shape one’s personality. They have created a specific picture of the artistic world, the dimensions of which are oriented to the peculiarities of children’s aesthetic perception. It is established that markers of regional identity (hydronyms, names of minerals, descriptions of landscape features, information about metallurgical and mining professions, tools, etc.) play a significant informational role in the texts. As a result of the analysis, it is determined that the regional identity of Kryvorizhzhya is based on the view of the region as one of the most powerful iron ore basins of the country. The introduction of these semantic models into the artistic world of children’s works contributes to the formation of a sense of regional identity in the minds of young readers.